Ship Design and Maintenance Computer Program. Tork (Ice Load Torque Calculations) - Lewis, Jack W.; Schumacher, Keith B. (1968)
TORK calculates the propeller load torque values resulting from striking a block of ice with the propeller blades and the hydro-dynamic propeller load torques as a function of shaft and vessel speed. TORK studies the effects which various propeller properties have on the total load torque to be overcome by propulsion machinery as a function of propeller speed and ship speed. The properties considered are propeller diameter, pitch-diameter ratio, blade thickness, hub diameter, strength of ice in crushing and in shear, number of blades, developed area ratio and percent of blade striking ice. (Author)